Effectiveness of teachers’ participation in a mathematics networked learning community in terms of students’ classroom environments and attitudes to mathematics in Singapore - Seto, Cynthia (Curtin University, 2014)
The effectiveness of students’ attitudes and the teachers’ participation in a networked learning community was evaluated in terms of learning environments created by these teachers in their mathematics classrooms. Data were collected from 375 Grade 5 students from five primary schools in Singapore. A pretest–posttest quasi-experimental design revealed that pretest–posttest changes were larger in magnitude for the experimental group than for the comparison group for every learning environment and attitude scale.